Factors associated with life satisfaction of adolescents living with employed and unemployed parents in Spain and Portugal: A person focused approach. (March 2020) - Moreno-Maldonado, C.; Jiménez-Iglesias, A.; Camacho, I.; Rivera, F.; Moreno, C.; Matos, M.G.
Highlights: Adolescents with unemployed fathers present lower life satisfaction, and even lower among those with both parents unemployed, compared to adolescents with both parents employed or only mothers unemployed. Family context showed to be a more important predictor of adolescent life satisfaction than friend satisfaction. All factors predicting adolescents life satisfaction were not equally important for the different groups of adolescents, separated according to their parental employment status. Family satisfaction plays a fundamental role in adolescents life satisfaction, especially for adolescents with both parents unemployed, who do not benefit from having a high friend satisfaction. Differences were found between boys and girls, as well as between Spain and Portugal in high life-satisfaction in all groups of adolescents with at least one employed parent. No sex- or country-based differences were found amongst adolescents with both parents unemployed. These results suggest that cultural and sex differences disappear in vulnerable situations. Abstract: Family and friend relationships may have a protective effect against the negative consequences of parental unemployment. However, whereas some studies have shown positive effects of family and peer relationships for all adolescents, others suggest that vulnerable groups have more difficulty benefiting from the positive effects of these relationships. The aim of this work was: (1) to analyze the association of different factors (satisfaction with family and friends, age, sex, and country) with life satisfaction in four groups of adolescents created according to their parents' employment status (both parents unemployed, unemployed mothers and employed fathers, unemployed fathers and employed mothers, and both parents unemployed); and (2) to examine differences between countries in the constellations of factors related to adolescents life satisfaction in each group. The sample was composed of 21, 081 adolescents from Portugal and Spain (11–16 years old) who participated in the 2014 edition of the HBSC study in both countries. Classification tree Analyses for the first objective, and general linear model and mean comparisons for the second, were performed. Results showed that some factors were associated with high life satisfaction in the majority of the adolescents: high family and friend satisfaction, being male, being younger, and being Spanish. However, for adolescents with both parents unemployed, life satisfaction was associated only with family satisfaction and age. Sex- and country-based differences were significant in all adolescents with at least one employed parent, but were not significant in adolescents with both parents unemployed. Findings highlight that family satisfaction plays a fundamental role in adolescent life satisfaction —especially for those with both parents unemployed— and that cultural and sex differences disappear in vulnerable situations.